A New Facility for Market Access Countries : The Short-Term Liquidity Facility -- proposed decision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This supplement sets forth the proposed decision that is needed to establish the Short-Term Liquidity Facility ('SLF') proposed in the main paper. It also summarizes key aspects and implications of this decision, and reviews the applicability to the SLF of other Fund policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet